S38 The role of the respiratory microbiome in Idiopathic pulmonary fibrosis. (14th November 2013) - Molyneaux, PL; Cox, MJ; Mallia, P; Johnston, SL; Moffatt, MF; Cookson, WOC; Maher, TM
Abstract : Introduction & Objectives: Idiopathic pulmonary fibrosis (IPF) is a progressive and invariably fatal disease thought to result from repeated episodes of alveolar injury in individuals with dysfunctional alveolar epithelial repair mechanisms. Although multiple environmental exposures have been suggested, there has been no systematic search for potential bacterial sources of alveolar injury. This study aimed to use culture independent techniques to characterise and confirm the presence of a respiratory microbiome in IPF. Methods: Sixty five newly diagnosed patients with IPF and twenty seven healthy controls were prospectively recruited and underwent bronchoscopy with bronchoalveolar lavage (BAL). Bacterial DNA was extracted and a variable region of the 16S ribosomal RNA gene (16S rRNA) amplified, allowing quantification of bacterial load by 16S rRNA qPCR and pyrosequencing on the Roche 454 platform. Data curation, denoising, chimaera removal and analysis were executed using QIIME (http://qiime.org/ ). Results: The IPF subjects had a mean age of 67 years and on average moderately severe disease (DLco 42 ± 11% predicted; FVC 77 ± 20% predicted). IPF subjects had a significantly higher bacterial load in BAL compared to controls ( P = 0.0063). The IPF microbiota was less diverse ( P = 0.0019) and less rich ( P = 0.015) compared to controls. While the microbiota of both IPF and healthy subjects were dominated by the phylum Firmicutes (51% and 53% respectively), the IPF microbiota contained significantly more Proteobacterial ( P = 0.003) sequences and fewer Actinobacteria ( P = 0.004). Within the IPF cohort there was also inter-individual heterogeneity with one subject's bacterial community dominated by a Burkholderia sp. (49% of total 16S sequences) and another with an abundance of a Moraxella sp. (21%). Conclusions: We present the molecular characterisation of the airway microbiota in IPF, providing evidence that the lower airways in this disease are not sterile and identifying potentially pathogenic respiratory organisms previously not associated with the disease. The higher bacterial burden and differences in the composition of the respiratory bacterial communities in IPF may provide a low level antigenic stimulus for repetitive alveolar injury and thus be involved in the pathogenesis and/or progression of the disease.